Spellman's standard handbook for wastewater operators : intermediate level - Spellman, Frank R. (Hoboken, New Jersey : CRC Press, 2011)
Up to date and current with the latest technology, Spellman's Standard Handbook for Wastewater Operators: Volume II, Intermediate Level, Second Edition provides a study guide and resource in a compact format. This second of three volumes contains a compilation of wastewater treatment information, data, operational material, process control procedures and problem solving, safety and health information, new trends in wastewater treatment administration and technology, and numerous sample problem-solving practice sets, many based on actual tests. New in the Second Edition: Chapter on operator saf
Front cover; Table of Contents; Preface, 2nd Edition; About the Author; Chapter 1: Operator Safety; Chapter 2: Water Hydraulics; Chapter 3: Hydraulic Machines: Pump s; Chapter 4: Wastewater Conveyance; Chapter 5: Wastewater Collection and Preliminary Treatment; Chapter 6: Primary Treatment(Sedimentation); Chapter 7: SecondaryTreatment; Chapter 8: Activated Sludge Process; Chapter 9: Disinfection; Chapter 10: Solids Handling; Chapter 11: Permits, Records, and Reports; Chapter 12: Final Review Exam; Appendix A: Answers to Chapter Review Questions. Appendix B: Answers to Final Review Exam(Chapter 12)Index; Back cover.
Includes index.
Keywords: ENVIRONMENTAL STUDIES